Pneumomediastinum and Spontaneous Subcutaneous Emphysema in COVID-19 Patients Using High-Flow Nasal Cannula (HFNC) - Suhadayanti, Rizki; Fatoni, Arie Zainul; Jaya, Wiwi; Asmoro, Aswoco Andyk (Jurnal Respirologi Indonesia, 2024)
Background: Spontaneous pneumothorax, pneumomediastinum, and subcutaneous emphysema are rare complications that occur without mechanical ventilation, namely 0.81% of all COVID-19 patients. During the COVID-19 pandemic, high-flow nasal cannulas (HFNC) were used to support respiratory failure in critically ill patients. However, there have been no clinical trials explaining its safety and effectiveness. Hypoxemic normocapnic respiratory failure is an indicator of HFNC use. This study reports a case of associated spontaneous subcutaneous pneumomediastinum and emphysema in a COVID-19 patient using HFNC.Case: A 30-year-old male patient came to the hospital with a chief complaint of increasingly severe shortness of breath and confirmed COVID-19. Physical examination revealed a good airway, spontaneous breathing with a frequency of 28 times/minute; SpO2 of 97% with HFNC Flow 60 and FiO2 60%; blood pressure of 102/69 mmHg; and heart rate of 65 beats per minute. On the second day of treatment in the ICU, the patient did not experience desaturation or hypotension. Patent airway, spontaneous breathing, and oxygenation initiated using NRM 10lpm with a target SpO2 of 97%, RR at 30-32x/minute. On the fifth day, desaturation and hypotension were no longer observed.Discussion: Real-Time Reverse Transcriptase (RT)–PCR Diagnostic Panel detects SARS-CoV-2 in respiratory samples. Chest CT scans show viral pneumonia. Subcutaneous emphysema (SE) and pneumomediastinum cause breathing issues. Severe COVID-19 is treated with antivirals, vitamins, and oxygen therapy. Pneumomediastinum or subcutaneous emphysema may occur due to prolonged non-invasive ventilation but is generally self-limited.Conclusion: Clinical improvement was found in COVID-19 patients with pneumomediastinum and spontaneous subcutaneous emphysema using HFNC.